PENGARUH KOMPETENSI PERSONAL TERHADAP KESIAPAN PERUBAHAN DALAM INDUSTRI 4.0 - Mochammad Harry Febriandono; Fitrian Harry Nuzul Mulia; Noor Hidyat Iswara (Jurnal TAM (Technology Acceptance Model), 2019)
To overcome the advancement of industry 4.0, adequate competence and knowledge are needed. Change readiness must be applied by the company to be applied to the advancement of existing technology. Automation continues and increases the ability of employees also increases. The challenge that will be faced is how to manage human resources in a company that prepares employees to improve their personal abilities in more complex processes and maintain work in a changing work environment. Personal competence is one of the competencies that employees must improve in preparation for improving industry 4.0 to support the changes that occur. In this journal, researchers used quantitative methods and sought information about what factors could be a reference in the readiness of human resources in the 4.0 digitization era. In this study it was found that employee flexibility, successful challenges, and the challenges of the factors that most influence the company in dealing with industry 4.0.